2014
DOI: 10.1038/ki.2013.525
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of proximal tubular suppressor of cytokine signaling 3 enhances tubular cell cycling and modifies macrophage phenotype during acute kidney injury

Abstract: Suppressor of cytokine signaling 3 (SOCS-3) is an important intracellular negative regulator of several signaling pathways. We found that SOCS-3 is highly expressed in renal proximal tubules during acute kidney injury. To test the impact of this, conditional proximal tubular knockout mice (SOCS-3(sglt2Δ/sglt2Δ)) were created. These mice had better kidney function than their wild-type counterparts in aristolochic acid nephropathy and after ischemia/reperfusion injury. Kidneys of these knockout mice showed signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…Accumulating experimental evidence indicates that macrophage phenotypes may drive kidney injury and fibrosis [17]. We examined changes in macrophage phenotypes further.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating experimental evidence indicates that macrophage phenotypes may drive kidney injury and fibrosis [17]. We examined changes in macrophage phenotypes further.…”
Section: Resultsmentioning
confidence: 99%
“…2), we wanted to determine if loss of Sav1 affects the response to injury by AAN. We administered AA to Ctrl and KS mice at a dose of 5 mg/kg of body weight, which was previously shown to result in mild to negligible AKI in normal healthy mice (51). Intraperitoneal introduction of AA into KS mice 3 weeks after ablation of Sav1 expression resulted in dramatic increases in the expression levels of all profibrotic genes (Col1a1, Col3a1, Col4a1, Fn, Tgf␤1, and Vimentin) examined compared to those in AA-treated Ctrl mice with no Sav1 loss ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These proteins may serve a special and pleiotropic biological function on immune regulation, hematopoietic stem cells, cancer, nervous system and embryonic development (25). Previous studies have shown that the JAK/STAT signal transduction pathways are involved in the development of the central nervous system and nerve cell proliferation, survival, differentiation, and they are closely associated with brain tumors, central nervous system diseases, including cerebral ischemia, and pathological physiological processes (26). The present study found that ursolic acid treatment reduced the increase of the protein expression levels of p-STAT3 in I/R-IAKI rats.…”
Section: Discussionmentioning
confidence: 99%